Neighborhood Accountability Boards: The Strength of Weak Practices and Prospects for a “Community Building” Restorative Model - Mara Schiff; Gordon Bazemore; Martha Brown (Washington University Journal of Law & Policy, 2011)
The Article focuses on neighborhood accountability boards (NABs) as restorative justice programs. Examples of NABs in communities include victim-offender mediation (VOM), peacemaking circles, and social support groups for offenders and victims. The authors discuss how NABs lessen the conditions that foster crime and provide community support for at-risk people.
Keywords: Restorative justice; Social networks; Conflict management; Community support; Community centers